A content analysis of the editorial cartoons of Philippine Daily Inquirer and its editorial stand on the Mindanao conflict - Damaso, Jaclyn R. 1981-
The study focused on how the Philippine Daily Inquirer conveyed its stand on the year 2000 Mindanao conflict through its editorial cartoons. Reputed to be the most critical of the government, the researchers wanted to establish that through analysis of the editorial cartoons. The study is also geared towards the establishment of how the newspaper conveyed the image of the warring factions involved, namely the government and the rebel group Abu Sayaff. The study also traced the history of the Mindanao conflict to establish the connection of the present conflict with the transformation of Muslim groups from just being 'separatist' groups to 'rebel' groups. The researchers used content analysis as the primary method of research for the study. There were 41 editorial cartoons analyzed with respect to the caricatures, objects, and captions used in them. The researchers' main source of data was the University of the Philippines' Main Library and the UP-CMC Library. The newspaper used was the Philippine Daily Inquirer. This study showed that the Inquirer portrayed the government, the rebel groups and the Mindanao conflict as a whole as being 'senseless' and only brought negative effects on the hostages, civilians, innocent, country's image to the international community, and also to the children who are able to watch the media coverage on television and have read them in newspapers as well. The editorial cartoons established the Inquirer as critical of the government, as what their present image is. There is consistency in the newspaper's reportage of the issue and its editorial stand.